A metal-vacancy-solid-solution NiAlP nanowall array bifunctional electrocatalyst for exceptional all-pH overall water splitting. Issue 20 (18th April 2018) - Cheng, Weiren; Zhang, Hui; Zhao, Xu; Su, Hui; Tang, Fumin; Tian, Jie; Liu, Qinghua
Abstract : We design a 3D metal-vacancy-solid-solution NiAlδ P nanowall array bifunctional electrocatalyst, which is highly efficient in pH-universal overall water splitting. Abstract : The development of active and durable bifunctional electrocatalysts for overall water splitting in a wide pH range is highly desirable for industrial water electrolysis. Herein, we develop a new type of 3D metal-vacancy solid-solution NiAlP nanowall array synthesized by a combination of selective alkali-etching and phosphorization strategies as a highly-active and earth-abundant all-pH bifunctional electrocatalyst for efficient overall water splitting. These metal-vacancy NiAlδ P nanowall arrays as both the anode and cathode are highly efficient in overall-water-splitting catalysis, realizing 10 mA cm −2 at quite low cell voltages of 1.50–1.70 V for pH = 0–14. In particular, the NiAlδ P nanowall arrays could achieve an outstanding overall water splitting activity in acidic electrolyte (pH = 0) with high turnover frequencies of ∼11 000 H2 per h and ∼5000 O2 per h at 50 and 300 mV overpotentials for the HER and OER, respectively, far exceeding those of the best noble-metal-free catalysts and the Pt/C–RuO2 combination.